H2020 Cultural Heritage Project with Outstanding Contribution to Sustainable Development - Skarlatos, Dimitrios (My University, 2026)
ICT-CH Workshop ‘Common challenges and perspectives for Digital Cultural Heritage in H2020 projects’, which took place in Brussels, European Research Council building 14th November 2018, organized by Directorate General for Research and Innovation (DG RTD). There, the iMARECULTURE project won the award for the H2020 Cultural Heritage Project with Outstanding Contribution to Sustainable Development
Keywords: Sciences